The Reporting of Sudanese Refugee Movements to Chad on Aljazeera.net: A Critical Discourse Analysis from Theo Van Leeuwen's Perspective - Nugraha, Muhammad Riyadi; Al Anshory, Abdul Muntaqim (LP2M IAIN Sultan Amai Gorontalo, 2025)
Background: The movement of refugees from Sudan to Chad is one of the global issues in the complex dynamics of the Middle East. News media plays a strategic role in shaping public understanding through discourse. Aims: This research aims to reveal the discourse strategy in Aljazeera.net's news coverage of the Sudanese refugee crisis, based on Theo Van Leeuwen's Critical Discourse Analysis. Methods: This research used a qualitative descriptive method. The data sources used in this research were news texts about the displacement of Sudanese people to Chad on Aljazeera.net, along with various supporting literature for analysis. The data collection techniques used are reading and note-taking methods. In addition, the data analysis technique involves data condensation, data presentation, and conclusion drawing. Results: The results of this study revealed that the news coverage is presented factually and fairly, following the exclusion and inclusion strategies, where these strategies help readers assess the quality of the news. Implications: This study implies that it provides readers with a deeper understanding of how news texts convey certain issues and can help policymakers understand media bias and highlight the importance of neutrality in reporting.